Beta-2-adrenoreceptor polymorphism at position 16 determines the clinical severity of chronic obstructive pulmonary disease. (April 2017) - Emeryk-Maksymiuk, Justyna; Emeryk, Andrzej; Krawczyk, Paweł; Wojas-Krawczyk, Kamila; Milanowski, Janusz
Abstract: The Arg/Arg homozygosity at codon 16 of the beta-2-adrenoreceptor ( ADRB2 ) gene has been thought to predispose asthma patients to a poorer therapeutic response to beta-2-mimetics, or to worse control of the disease. In contrast, the results of the studies analysing the effect of ADRB2 polymorphisms on the response to beta-2-adrenoreceptor agonists in chronic obstructive pulmonary disease (COPD) patients are sparse and inconclusive. The aim of this research was to verify if p.Arg16Gly (c.46A > G) and p.Gly27Glu (c.79G > C) single nucleotide polymorphisms (SNPs) exert a negative effect on the selected clinical indicators of COPD. The SNPs of the ADRB2 were identified by multiplex allele-specific PCR on DNA isolated from the venous blood leukocytes of 92 patients with stable grade COPD. In addition, all of the patients were asked about the course of COPD during the 12 months preceding the study, including the frequency of exacerbations requiring hospitalisation, the number of antibiotic therapy courses given due to the lower respiratory tract infection, and the number of courses of systemic corticosteroid therapy administered due to the exacerbation of COPD. Arg/Arg homozygotes at codon 16 required at least two courses of antibiotic therapy administered as a result of a lower respiratory tract infection significantly more frequently than carriers of other polymorphic variants of the ADRB2 . Moreover, they were the only ones who required three or more courses of corticosteroid therapy due to COPD exacerbation. No significant relationships were observed between the polymorphism at codon 27 and the analysed clinical indicators of COPD severity. These data suggested that Arg/Arg homozygosity at codon 16 of the ADRB2 gene predisposes patients to a clinically more severe course of COPD.